Regional Spatial Development Framework for Saldanha Bay Municipality: Pursuing a more Ecologically Integrated Future - Le Grange, Louis (School of Architecture, Planning and Geomatics, 2019)
This study has sought to understand how spatial planning can be utilized as a tool to aid the transition to a more ecologically resilient future through better integrating natural resource management and spatial planning. Nature profoundly influences the structure and form of Saldanha Bay Municipality. This is based on the premise that nature is not situated at the forefront of development and is not adequately addressed in spatial planning - our relationship with nature needs to change. Strategic spatial planning is a long term future imagined. Unlike conventional land use management, spatial planning is well-positioned to resolve conflicts and tensions through in-depth analysis, direction, guidance and then strategic implementation. With the guidance of multiple policies, the personal beliefs of a planner and the incorporation of the interests of a variety of stakeholders, a future that is conducive to all is possible. In light of this, the main objective of this study was to integrate the 2011 Spatial Development Framework and the 2015 Environmental Management Framework of Saldanha Bay Municipality in order to find gaps and contestations which will help produce an improved and better-integrated ecologically mindful Regional Spatial Development Framework for Saldanha Bay Municipality. This study has undertaken a review of international literature to theoretically locate this study. This is followed by a contextual spatial and policy analysis of Saldanha Bay Municipality, which was predominantly focused on the findings of the 2015 EMF and 2011 SDF in order to better understand the key priorities with regards to the environment in the region. Using this as a platform to guide appropriate intervention, a Regional Spatial Development Framework (RSDF) has been created to propose a new nature-based development path. This plan is governed by the principles of reverence, intergenerational equity, interconnectedness, intrinsic value and individual responsibility. By recognizing the spatial relationships between people, their activities and nature this RSDF offers an opportunity to promote a more integrated and harmonized future. This is done using the key environmental layers of the 2015 EMF as the main platform to guide development towards better ecological resilience and adaption in the region. The key layers of the 2015 EMF are the” Keep Assets Intact”, “Develop with Care: Valued Resources” and “Develop with Care: Restrictive Conditions or Constraints” which indicate all the environmental attributes in the region. By understanding the environmental context, the researcher formulated three management frameworks from which key strategic interventions were developed in order to accommodate these environmental attributes and guide the vision of the RSDF. The landscape and natural resource management framework consists of the strategies of ecological remnants, diversifying dryland agriculture, coastline protection and enhancement, and lastly catchment management initiatives. All these strategies are directed at and fundamentally pursue the protection, enhancement, conservation and regeneration of ecosystems and biodiversity in the region. The economic development management framework consists of the strategies of renewable energy, eco industries and the IDZ. These strategies focus on the advancement of the local economy through sustainable and ecologically adaptive strategies. The site and settlement management framework consists of the strategies of townscape, reduce point source pollution and sustainable human settlements. These strategies focus on the local sense of place and predominantly the upgrading of infrastructure within settlements in the region. They are placed within a phasing framework for optimized and strategic intervention. All these strategies aim to create a more life-sustaining region through integrating and harmonising the relationship between people and nature, by establishing the importance and qualities of nature. Therefore, by implementing strategies that are spatially designated across the region and that focus on environmental prosperity and the integration of people and nature, it could be possible to transition to an increasingly ecologically secure future in Saldanha Bay Municipality where there is improved social and ecological health, local prosperity and a region where the natural landscape flourishes.